Gender equality in German constitutional law - Michael Wrase (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
The fundamental right to gender equality has played an important role in Germany's more recent constitutional history. The rulings of the Federal Constitutional Court (FCC, Bundesverfassungsgericht) and other courts have developed doctrinal standards that are relevant to anti-discrimination legislation overall. This article provides a brief history of gender equality in the German Basic Law (Grundgesetz) and its concretization in key Constitutional Court decisions from 1949 until today. A special emphasis is on the legal doctrine of non-discrimination and on the influence of feminist legal scholars. The article concludes with a discussion of affirmative action measures from the perspective of constitutional law.
Keywords: 300